Response rates of hepatic arterial infusion pump therapy in patients with metastatic colorectal cancer liver metastases refractory to all standard chemotherapies. Issue 6 (26th August 2016) - Cercek, Andrea; Boucher, Taryn M.; Gluskin, Jill S.; Aguiló, Ariel; Chou, Joanne F.; Connell, Louise C.; Capanu, Marinela; Reidy‐Lagunes, Diane; D'Angelica, Michael; Kemeny, Nancy E.
Abstract : Background and Objectives: To evaluate the role of hepatic arterial infusion (HAI) in patients with metastatic colorectal cancer (mCRC) liver metastases (LM) refractory to oxaliplatin, irinotecan, and fluorouracil‐based treatments. Methods: A search identified patients with mCRC treated after tumor progression on at least three standard systemic therapies. Results: One hundred and ten patients met criteria for inclusion (i.e., progression on at least three standard agents). Fifty seven patients had LM‐only and 53 patients had LM and low volume extrahepatic metastases (LME). Patients with LM‐only and LME had a response rate (RR) of 33% and 36%, median survival of 20 months and 11.4 months, respectively. Patients with LM‐only had progression free survival of 6 months and hepatic progression free survival of 7.56 months. In a secondary analysis, 46 patients were RECIST‐refractory to all standard therapies: LM‐only (n = 24) and LME (n = 22). LM‐only and LME had a RR of 29% and 36%, and median survival 17.2 months and 9.1 months, respectively. Conclusions: Patients with refractory mCRC LM can achieve a response to HAI resulting in antitumor activity and improvement in survival. Responses are rarely seen in such heavily treated patients with systemic therapy alone, suggesting a regional directed approach is useful. J. Surg. Oncol. 2016;114:655–663 . © 2016 Wiley Periodicals, Inc.